PENGARUH CELEBRITY ENDORSEMENT, TESTIMONI, DAN KEAMANAN TERHADAP KEPUTUSAN PEMBELIAN PADA ONLINE SHOP BLIBLI.com (Studi Pada Mahasiswa FEB UNISMA Angkatan Tahun 2016) - Arif Agung Saputro; Nur Hidayati; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to determine the analysis of the influence of celebrity endorsement on purchasing decisions at Blibli.com online shop, analysis of the influence of testimonials on purchasing decisions at Blibli.com online shop, and analysis of the effect of security on purchasing decisions at Blibli.com online shop. This research is a type of explanatory research with a quantitative approach. The research subjects were 81 active students of Islamic University of Malang. Data collection method is done by using a questionnaire. The analytical method used is the validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, hypothesis test, and the coefficient of determination test. The results show that celebrity endorsement influences purchasing decisions at Blibli.com online shop, testimonials do not affect purchasing decisions at Blibli.com online shop, and security influences purchasing decisions at Blibli.com online shop.Keywords: celebrity endorsement, testimonials, security, purchasing decisions at Blibli.com online shop